Dampak Good Corporate Governance, Profitabilitas dan Kualitas Audit terhadap Manajemen Laba pada Perusahaan yang terdaftar di Bursa Efek Indonesia - Pinem, Diya Chris Dilla Br; Arjuna Sembiring, Bangkit; Yunior, Khomeiny; Fauzi, Fauzi (Journal of Management and Bussines (JOMB), 2024)
This study aims to test and analyze the effect of GCG, profitability and audit quality on earnings management in basic and chemical industry companies listed on the IDX in 2019-2022. This study uses a quantitative approach, namely hypothesis testing. The data analysis method used is multiple regression analysis. The population used is all basic and chemical industry companies listed on the IDX in 2019-2022, and sampling using the purposive sampling method of 21 companies. The results of the study indicate that motivation does not have a significant effect on the performance of Jambesari Health Center employees. Partially throughout the 2019-2022 period, the GCG ratio in basic and chemical industry companies listed on the IDX in 2019-2022 does not have a significant effect on earnings management, as well as the profitability ratio and earnings quality in basic and chemical industry companies listed on the IDX in 2019-2022 do not have a significant effect on earnings management. Keywords: Good Corporate Governance, Audit Quality, Earnings Management, Profitability